The Last r Locus Unveiled: T4 RIII Is a Cytoplasmic Antiholin - Chen, Yi; Young, Ry (Journal of bacteriology, 2016)
The latent period of phage T4, normally ∼25 min, can be extended indefinitely if the infected cell is superinfected after 5 min. This phenomenon, designated lysis inhibition (LIN), was first described in the 1940s and is genetically defined by mutations in diverse T4 r genes. RI, the main effector of LIN, has been shown to be secreted to the periplasm, where, upon activation by superinfection with a T-even virion, it binds to the C-terminal periplasmic domain of the T4 holin T and blocks its lethal permeabilization of the cytoplasmic membrane. Another r locus, rIII , has been the subject of conflicting reports. In this study, we show that RIII, an 82-amino-acid protein, is also required for LIN in both Escherichia coli B strains and E. coli K-12 strains. In T4Δ rIII infections, LIN was briefly established but was unstable. The overexpression of a cloned rIII gene alone impeded T-mediated lysis temporarily. However, coexpression of rIII and rI resulted in a stable LIN state. Bacterial two-hybrid assays and pulldown assays showed that RIII interacts with the cytoplasmic N terminus of T, which is a critical domain for holin function. We conclude that RIII is a T4 antiholin that blocks membrane hole formation by interacting directly with the holin. Accordingly, we propose an augmented model for T4 LIN that involves the stabilization of a complex of three proteins in two compartments of the cell: RI interacting with the C terminus of T in the periplasm and RIII interacting with the N terminus of T in the cytoplasm. IMPORTANCE Lysis inhibition is a unique feature of phage T4 in response to environmental conditions, effected by the antiholin RI, which binds to the periplasmic domain of the T holin and blocks its hole-forming function. Here we report that the T4 gene rIII encodes a cytoplasmic antiholin that, together with the main antiholin, RI, inhibits holin T by forming a complex of three proteins spanning two cell compartments.